UNLOCKING THE HIDDEN SIDE OF ECONOMIC ABUSE IN MALAYSIA - Chuong Shing, Chin; Shirly Siew Ling, Wong; Keng Sheng, Chew; Nur Amira Aina, Zulkarnain (UNIMAS Publisher, 2022)
Economic abuse is an abusive tactic commonly employed by a perpetrator to diminish the economic security and potential self-sufficiency of victims. While most studies have examined economic abuse from intimate relationships, scant research has documented non-intimate relationships (e.g., between parents and children). Apart from that, the role of economic abuse in triggering domestic violence in Malaysia remains underexplored. Therefore, the present study seeks to investigate the association between economic abuse and mental distress among Malaysian students, in addition with the role of financial distress. Therefore, a crosssectional analysis was performed using an online-based survey with 126 respondents. Multivariate regression analysis was performed to examine the interrelation effects between the variables using structural equation modeling (SEM). Findings indicated that economic abuse is positively associated with financial distress and mental distress among students. Furthermore, financial distress has a significant mediating effect on the relationship between economic abuse and mental distress. Therefore, there is a need for practitioners to cooperate with government agencies to establish a comprehensive economic empowerment program to assist victims.